FOMO PHENOMENON IN GEN Z INVESTMENT BEHAVIOR: COMPARISON OF CONVENTIONAL AND SHARIA INVESTMENT INSTRUMENTS - Gladis Jelita; Laylan Syafina; Muhammad Lathief Ilhamy Nasution (EP FEB UNS, 2026)
This research analyzes the influence of Fear of Missing Out (FOMO) on the investment behavior of Gen Z and compares its manifestations in conventional and sharia investment instruments thru a descriptive qualitative approach with in-depth interviews. The research results show that FOMO drives more impulsive investment decisions in conventional instruments, primarily due to the urge to follow trends and a short-term profit orientation. On the other hand, in Sharia investments, the influence of FOMO tends to be more controlled due to ethical considerations, principles of prudence, and Sharia compliance. Financial literacy, particularly Sharia financial literacy, also plays an important role in moderating the influence of FOMO by enhancing the rationality and risk awareness of investors. These findings affirm that the characteristics of investment instruments and the level of financial literacy influence Gen Z's response to behavioral biases in investment decision-making.